Sektor Pelayanan Publik Sebagai Sarana Korupsi di Kota Medan - Nasution, Rasina Padeni; Batuabara, Indah Sakinah; Rahma, Annisa Aulia; Aila, Nurul; Amaliah, Rizky; Butarbutar, Rini Andriani (At-Tadris: Journal of Islamic Education, 2023)
The purpose of this investigation is to ascertain the scope of the Ombudsman's function as a state institution with the authority to oversee the implementation of public services organized by state and government administrators. These public services include those held by State-Owned Enterprises, Regional-Owned Enterprises, and State-Owned Legal Entities, as well as private entities or individuals tasked with managing specific public services in the Medan City region.An interview and observation-based qualitative descriptive research approach was utilized in this study. "Key informants, main informants, and additional informants" were utilized in the study. This study's findings explain how the Ombudsman of the Republic of Indonesia and the Kedan Ombudsman were able to set up a supervisory mechanism that was appropriate for its responsibilities. The partnership process that has been established between the Representative for North Sumatra of the Ombudsman of the Republic of Indonesia and the Representative for North Sumatra of the Kedan Ombudsman demonstrates this. The goal of this partnership, which is to improve the quality of public services in the Medan City region, will remain a priority.